People's Republic of China Financial Sector Assessment Program : Basel Core Principles for Effective Banking Supervision - International Monetary Fund (Washington, DC, 2017)
The China Banking Regulatory Commission (CBRC) has maintained its momentum in regulation and supervision in the face of exceptional growth in scale and increasing complexity of the banking system. Equally, the CBRC has risen to the demands of the international regulatory reform agenda, delivering timely revisions to its body of regulations and maturing its supervisory practices through investing in essential new skills, enhancing methodologies, and broadening its interactions with the industry. In this context, the clarity of supervisory requirements and expectations communicated to the industry is a strength of the CBRC. Recent organizational reforms, in 2015, building on other internal reforms, will serve the CBRC well in delivering its supervisory mandate. While pursuit of financial stability is recognized as fundamentally important, concerns must be acknowledged as to whether the CBRC would, in practice, always be able to act on its primary, stability, objective, especially if government policies, whether focused growth and expansion, or social protection, conflicted with prudential considerations. The China Banking Regulatory Commission (CBRC) has achieved a high degree of compliance with the Basel Core Principles for Effective Banking Supervision (BCPs). Notwithstanding the revision to the BCP methodology, which raised the standards expected of supervisory authorities, the CBRC has demonstrated progress in almost all areas. Nevertheless, further maturing is needed, and taken together the recommendations of this report seek to support the CBRC in developing deeper and more comprehensive diagnostic capabilities, which ought to facilitate early, effective and preventative actions as necessary. It is essential that the CBRC’s achievements in recent years are consolidated as new challenges and complexities in the system will continue to emerge. In particular, it is essential that the CBRC obtain the resources to expand its range and depth of skills before developments in the industry leave it unable to maintain meaningful oversight and authority, not least of the four Global Systemically Important Banks (GSIBs). Building on the supervisory vision expressed in prestige CBRC publications such as the Annual Report, a detailed forward strategy for supervision, covering three to five years, would serve as a vehicle for the CBRC to articulate its case for resources.